On Interval Edge Colorings of Harary Graphs H2n2;2n - Kamalian, Rafayel R.; Petrosyan, Petros A . (Mathematical Problems of Computer Science, 2021)
The problems of existence and construction of interval edge colorings of Harary graphs H2n2;2n are investigated. Bounds are found for the possible number of colors in interval edge colorings of H2n2;2n.